An Automated Heteroduplex Assay for the PlA Polymorphism of Glycoprotein IIb/IIIa, Multiplexed with Two Prothrombotic Genetic Markers - O’Connor, Fiona; Fitzgerald, Desmond J.; Murphy, Ronan P. (Thrombosis and Haemostasis, 2000)
Screening for the PlA polymorphism has been made faster and simpler with the advent of heteroduplex technology. Simultaneous screening for three common prothrombotic polymorphisms PlA, factor V Leiden, and MTHFR(C677T) has been achieved with multiplex heteroduplex analysis. We describe a quick and simple method for PlA heteroduplex probe production. The probe was multiplexed with heteroduplex probes for MTHFR(C677T) and factor V Leiden polymorphisms in a one tube assay, allowing rapid automated genotyping of all three. This automated multiplex assay was applied to a cohort of 165 patients and showed excellent correlation with gel-based assays, both PAGE and RFLP. This approach will facilitate the analysis of multiple polymorphisms in complex disease in large populations.
Keywords: PlA; factor V Leiden; thermolabile MTHFR polymorphisms; automated heteroduplex assay